Effectiveness of Modified Constraint Induced Movement Therapy along with Conventional Physiotherapy on upper extremity function for children with hemiplegic type of cerebral palsy - Rahman, Ehsanur (Journal of Medical Biomedical and Applied Sciences, 2017)
Objectives To determine the effectiveness of modified CIMT on upper extremity function for children with hemiplegic type of cerebral palsy(CP).DesignQuasi experimental research designParticipants and interventionsTwelve(12) children (age: 2 to 8 years) from pediatric physiotherapy clinics from Savar, CRP with hemiplegic type of cerebral palsy were included in this study. Modified constraint was applied to unaffected hand.The intervention was given for 3 hours/day including 30 minutes of therapy time and home program which could split into different sessions of no less than 30 minutes duration for consecutive two(2) weeks. Conventional physiotherapy treatment was also given this experimental group in official therapy session timeperiod.Main outcome measuresPre and Post outcome measure by using QUEST (Quality of upper extremity skill test) and PMAL (pediatric motor activity log) were taken.ResultsSignificant differences between Pre and Post values of all components of QUEST and PMAL (P<0.05) showing the effectiveness of MCIMT in improving upper extremity function and in ADL activities.ConclusionMCIMT is involved of intensive training of the affected arm and restriction of unaffected arm. It is used for improving manual function or ability in children with hemiplegic CP. This is statistically as well as clinically significant improvements in both motor function and functional use of the affected upper extremity in children between the ages of 2 and 8 years with hemiplegic CP.It is statistically proved that MCIMT therapy was effective for all QUEST components except protective extension.